Psychological Factors and Higher Branded Price to Purchase Decision of MS Glow Skin Care - Jayanti, Suci Etri; Rusmewahni, Rusmewahni; Siahaan, Rumiris; Sinurat, Mangasi; Ilham, Rico Nur (International Journal of Business, Economics & Financial Studies, 2024)
The beauty industry has evolved, with skincare becoming crucial for women. It protects against environmental factors and prevents issues caused by make-up. The Indonesian skincare market is growing, reflecting the increasing importance of skin health. This study investigates the influence of lifestyle, psychological factors, and pricing on MS Glow skincare product-purchasing decisions among students at the University of North Sumatra's Faculty of Education. Using primary data from 100 respondents, multiple linear regression analysis was employed to examine the relationships between the independent variables (lifestyle, psychological factors, and price) and the dependent (purchase decision) variables. This research aims to understand consumer behavior in skincare product acquisition, focusing on MS Glow. Contrary to expectations, price does not significantly influence purchase decisions. However, lifestyle and psychological factors play substantial roles, exhibiting positive and statistically significant relationships with the dependent variable. These findings challenge conventional wisdom about the importance of pricing in student consumer decision-making and highlight the need for lifestyle-oriented and psychologically driven marketing approaches in the skincare industry. This study contributes valuable insights into university students' decision-making processes for personal care products, enhancing the understanding of consumer behaviour in this demographic.